Software-assisted US/MRI fusion-targeted biopsy for prostate cancer - Angileri, Salvatore Alessio; Di Meglio, Letizia; Petrillo, Mario; Arrichiello, Antonio; Pandolfi, Marco; Rodà, Giovanni Maria; Granata, Giuseppe; Ierardi, Anna Maria; Donat, Daniela; Paolucci, Aldo; Carrafiello, Gianpaolo (Acta Biomedica Atenei Parmensis, 2020)
Background: Prostate cancer is the first cancer diagnosis in men. European Association of Urology (EAU) Guidelines for Prostate Cancer underline the importance of screening, performed through PSA testing on all men with more than 50 years of age and before on men with risk factors. The diagnosis is still histopathologic, and it is done on the basis of the findings on biopsy samples. Materials and Methods: Fusion biopsy is a relatively new technique that allows the operator to perform the biopsies in office instead of the MRI gantry, without losing the detection capability of MRI. The T2-wighted images obtained during a previous mpMRI are merged with the real-time ones of the TRUS. Results: Fusion biopsy in comparison with the systematic standard biopsy has a better detection rate of clinically significant cancers and of any cancers. Conclusion: EAU 2020 guidelines still do offer a list of indications of when the biopsy should be performed, but it still appeared to be overperformed. The aim of our study is to underline how, in accordance with the recent literature result, fusion biopsy has showed a better detection rate of any cancer and clinically significant disease with a reduced numbers of samplings, and no substantial difference between the multiple software.